Review Article: The Complementarities of Poverty Reduction, Equity, and Growth: A Perspective on the World Development Report 2006. - Collier, P; Dercon, S (2006)
This article has two related objectives. First, it offers a critique of the way poverty and inequality have become central in the development discourse of donors and international agencies. Second, it offers a review of the World Development Report 2006 on Equity and Development and its emphasis on the instrumental role of inequality in development. The reduction in poverty is obviously important in discussing and analyzing development, but it is only a proxy measure of what successful development achieves. As such, targeting it induces some errors just as it eliminates others. So central has the concept become, aided by the fact that it poses intriguing challenges of measurement, that these errors have been forgotten. The addition of equity as a concern unfortunately reinforces the errors that are made by privileging poverty, prioritizing strategies that reduce poverty in the short term over long-term development. The World Development Report 2006 overextends the role of inequality and redistribution in development processes by overemphasizing relevant but particular efficiency-equity complementarities, by conflating domestic and international equality issues, and by naively integrating economic and political equalities.